A study of the influence of vertical tyre force on rolling resistance coefficient and lateral slip stiffness coefficient using truck tyre model - Govardhan Raju, Bharath; Nobeling, Nicholas; Rajopadhye, Chirag; Tota, Pranay Damodhar (My University, 2021)
Tyres are an important component that affect the energy consumption and performance of all vehicles, including trucks. The vital properties of the tyre realising these phenomena are the rolling resistance and lateral slip stiffness, respectively. This project aims to investigate and understand the influence of vertical load on the rolling resistance coefficient and lateral slip stiffness and based on these investigations, evaluate the possibility of creating simple and physically interpretable yet tune-able tyre models. The lateral slip stiffness investigation involves modelling a physical tire model based on the brush model with parabolic pressure distribution and a curve-fit model based on the ’openPBS’ tool non-linear tyre model. These models are tuned to match the data extracted from the VTI experiments of test performed with a truck tyre on the tyre testing facility. The lateral slip stiffness generated using both models is compared with the experimental test data, and found that the curve-fit model presents a better approximation of the test data. However, dense measurement data in terms of more data sets for varying vertical loads as well as more number of measured lateral force vs. slip points for each vertical load data set will be required to confirm this conclusion. The variation of RRC with lifted and non-lifted axles is studied using test data availed from a report by Lennart Cider, discussing the rollout tests of two different trucks with lifted and non-lifted axles. A proposition of load independent wheel bearing torque loss is considered as an alternate explanation for the varying rolling resistance and a study conducted for the same shows that the friction losses in the wheel bearings could approximately account for around only 13.5% of the estimated change in rolling resistance. Hence this cause solely is an unlikely explanation of the difference in rolling resistance. A finite element study of the tyre contact patch and the vertical load offset could aid the understanding of this phenomena better.
Keywords: Truck tyre; tyre model; rolling resistance; slip stiffness; bearing loss